2010
DOI: 10.1074/jbc.m110.172866
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Repressor E4-binding Protein 4 (E4BP4) Regulates Metabolic Hormone Fibroblast Growth Factor 21 (FGF21) during Circadian Cycles and Feeding

Abstract: Fibroblast growth factor 21 (FGF21) is a potent antidiabetic and triglyceride-lowering hormone whose hepatic expression is highly responsive to food intake. FGF21 induction in the adaptive response to fasting has been well studied, but the molecular mechanism responsible for feeding-induced repression remains unknown. In this study, we demonstrate a novel link between FGF21 and a key circadian output protein, E4BP4. Expression of Fgf21 displays a circadian rhythm, which peaks during the fasting phase and is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
106
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 77 publications
8
106
2
Order By: Relevance
“…Previously, we identified Fgf21 as a direct circadian target of E4BP4 in hepatocytes (9). In the present study, we demonstrate that E4BP4 is an in vivo repressor of Fgf21 transcription during fasting-refeeding cycles.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…Previously, we identified Fgf21 as a direct circadian target of E4BP4 in hepatocytes (9). In the present study, we demonstrate that E4BP4 is an in vivo repressor of Fgf21 transcription during fasting-refeeding cycles.…”
supporting
confidence: 54%
“…Plasmids and Adenovirus Generation-Both E4BP4 overexpression and shRNA vectors were reported before (9). The adenovirus for Ad-E4bp4 (overexpression), Ad-shE4bp4 (knockdown), and Ad-shG9a (knockdown) were generated using the pAdEasy system (Agilent) and pAd-Block-it system (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have identified a clear link between the molecular clock and hepatic FGF21 signaling (60,61), including suppression of Fgf21 transcription by E4BP4, which is a direct Rev-erb␣ target in liver (60). In addition, Rev-erb␣ has been shown to modulate FGF21 expression in liver (62).…”
Section: Discussionmentioning
confidence: 99%